(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
India has become one of the prominent destinations for spiritual tourism with several international tourists visiting multiple spiritual tourist sites for their spiritual or religious fulfilment. Limited research exists that investigate in depth what really motivates an individual to take on a spiritual journey. Literature also demands enrichment in terms of challenges or barriers to a spiritual tourism. Feedback from the pilgrims can help shrine administration to effectively utilise the donor money in improving the facilities during the journey and experience of the spiritual tourist. Through this paper, we make an effort to address this gap by conducting in-depth interviews of pilgrims of two most prominent spiritual tourism sites in North India, analysing their narratives using interpretative methods. We present pilgrim’s feedback on the motivational aspects of their spiritual tourism as well as challenges encountered during the journey. Feedback from them is reported for enhanced experience.